New solvability conditions for a non-local boundary value problem for nonlinear functional differential equations - Oplustil, Z. (Нелінійні коливання, 2008)
New efficient conditions are obtained sufficient for the solvability as well as unique solvability of a nonlocal boundary-value problem for nonlinear functional differential equations.